2020
DOI: 10.1186/s40659-020-00313-3
|View full text |Cite|
|
Sign up to set email alerts
|

Increased glucose metabolism in Arid5b−/− skeletal muscle is associated with the down-regulation of TBC1 domain family member 1 (TBC1D1)

Abstract: Background Skeletal muscle has an important role in regulating whole-body energy homeostasis, and energy production depends on the efficient function of mitochondria. We demonstrated previously that AT-rich interactive domain 5b (Arid5b) knockout (Arid5b−/−) mice were lean and resistant to high-fat diet (HFD)-induced obesity. While a potential role of Arid5b in energy metabolism has been suggested in adipocytes and hepatocytes, the role of Arid5b in skeletal muscle metabolism has not been studied. Therefore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Functional enrichment analysis additionally indicated that myld-CpGs encompass a diverse range of receptor signalling, immune cell activation, chemokine and metabolic-related processes and pathways (Figure 1E). Although annotated to n=449 genes, we found AT-Rich Interaction Domain 5B (ARID5B), a transcriptional co factor which has been shown to regulate glucose metabolism (24), contained the most myld-CpGs (Figure 1F, Table S1)…”
mentioning
confidence: 99%
“…Functional enrichment analysis additionally indicated that myld-CpGs encompass a diverse range of receptor signalling, immune cell activation, chemokine and metabolic-related processes and pathways (Figure 1E). Although annotated to n=449 genes, we found AT-Rich Interaction Domain 5B (ARID5B), a transcriptional co factor which has been shown to regulate glucose metabolism (24), contained the most myld-CpGs (Figure 1F, Table S1)…”
mentioning
confidence: 99%
“…A total of 11 candidate growth-related genes from 28 growth-related QTL regions were identified d by QTL mapping. It has been reported that TBC1 domain family member 1 ( tbcd1 ) is involved in the regulation of glucose transporter protein 4 transport and glucose uptake in adipocytes and skeletal muscle ( Treebak et al, 2010 ), and downregulation of tbcd1 is associated with enhanced glucose metabolism in mouse skeletal muscle ( Okazaki et al, 2020 ). Golgin subfamily B member 1 ( golgb1 ) encodes golgi-associated large transmembrane protein, and it suggests that a novel 65bp was significantly associated with chicken body weight and significantly associated with neck weight and abdominal fat weight ( Linstedt and Hauri, 1993 ; Fu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified a mistake in the acknowledgement section.…”
Section: Correction To: Biol Res (2020) 53:45 Https://doiorg/101186/s40659-020-00313-3mentioning
confidence: 99%